PSYCHO-EMOTIONAL SUPPORT OF YOUTH IN THE ACTIVITIES OF OUT-OF-SCHOOL INSTITUTIONS IN CRISIS CONDITIONS - Sochynskyi, Andrii; Feshchuk, Volodymyr (Журнал Педагогики и психологии в современном образовании, 2024)
Current world events, such as the COVID-19 pandemic, the war in Ukraine and other crises, have a significant impact on the psycho-emotional state of people, especially young people. In conditions of uncertainty, fear and anxiety, young people need special support and help. Out-of-school institutions play an important role in this support, offering young people opportunities for development, communication and self-actualization.